A Case-Control Study of the Relationship Between SLC22A3-LPAL2-LPA Gene Cluster Polymorphism and Coronary Artery Disease in the Han Chinese Population - Song, Zi-Kai (Iran Red Crescent Med J, 2016)
BACKGROUND: Mutations in the solute carrier family 22 member 3 (SLC22A3), lipoprotein (a)-like 2 (LPAL2), and the lipoprotein (a) (LPA) gene cluster, which encodes apolipoprotein (a) [apo (a)] of the lipoprotein (a) [Lp (a)] lipoprotein particle, have been suggested to contribute to the risk of coronary artery disease (CAD), but the precise variants of this gene cluster have not yet been identified in Chinese populations. OBJECTIVES: We sought to investigate the association between SLC22A3-LPAL2-LPA gene cluster polymorphisms and the risk of CAD in the Han Chinese population. PATIENTS AND METHODS: We recruited 551 CAD patients and 544 healthy controls for this case-control study. Four SNPs (rs9346816, rs2221750, rs3127596, and rs9364559) were genotyped in real time using the MassARRAY system (Sequenom; USA) in the SLC22A3-LPAL2-LPA gene cluster. All subjects were Chinese and of Han descent, and were recruited from the First Hospital of Jilin University based on convenience sampling from June 2009 to September 2012. RESULTS: The frequency of the minor allele G (34.8%) in rs9364559 was significantly higher in the CAD patients than in the healthy controls (29.4%) (P = 0.006). There was genotypic association between rs9364559 and CAD (P = 0.022), and these results still remained significant after adjustment for the conventional CAD risk factors through forward logistic regression analysis (P = 0.020, P = 0.019). Haplotype analyses from different blocks indicated that 11 haplotypes were associated with the risk of CAD. Seven haplotypes were associated with a reduced risk of CAD, whereas four haplotypes were associated with an increased risk of CAD. CONCLUSIONS: Rs9364559 in the LPA gene may contribute to the risk of CAD in the Han Chinese population; haplotypes which contain rs9346816-G were all associated with an increased risk of CAD in this study.